THE PROBLEM OF RATIONAL CHOICE OF OPTIONS OF TRANSPORT COMPANY DIVERSIFICATION - G. A. Kryzhanovskii; V. P. Maslakov; I. A. Ilinykh (Научный вестник МГТУ ГА, 2017)
The necessity of using of heuristic methods take account of uncertainties in each of the transport company activities when choosing a rational variant of the vector control of dynamic processes related to performance indicators, built on the basis of poly-criteria evaluation.